PERENDERAN ULANG VIDEO DENGAN PENAMBAHAN TEKNIK LOWER THIRD PADA PROFIL INSTANSI KAMPUS STMIK DHARMA WACANA - Purnomo, Eko; Islami, Muhammad Reza Redo (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Nowadays, videos are familiar to many people, but most people only think that an incident can be documented without understanding the original explanation. Initially video was a technology for sending electronic signals from a moving image and video was also included in the multimedia group, besides that video was also included as a medium for conveying information. Basically, every company, campus or school agency has a video which will introduce and provide information to everyone. In this study, it focuses on the application or utilization of the Lower Third technique on the video of the STMIK Dharma Wacana campus institution. The Lower Third technique is a technique that combines text with graphic elements that are placed at the bottom of the screen or video. Which aims to provide information to everyone. The research method applied, namely, using primary and secondary methods, is a method in which both review or analyze and collect data either by way of direct interviews or studying theories related to the technique. The results of this study show that it can provide information that is more actual, interesting and accurate, and can find out what the lower third technique is.